2020
DOI: 10.7759/cureus.11862
|View full text |Cite
|
Sign up to set email alerts
|

Findings of Esophagogastroduodenoscopy in Patients Suspected of Upper Gastrointestinal Bleeding Referred to the Main Endoscopy Unit at King Fahad Specialist Hospital

Abstract: Introduction Upper gastrointestinal bleeding (UGIB) is defined as any blood loss originating from the esophagus, stomach or the proximal duodenum above the ligament of Treitz. Ethnic trends regarding the causes of UGIB have been reported. The aim of this study was to identify the most common causes of UGIB among patients residing in Tabuk city, Saudi Arabia. Methods We have conducted a retrospective descriptive cohort study at King Fahad Specialist Hospital (KFSH), Tabuk, Saudi Arabia. All adult patients above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…10% had history of NSAIDS use and 5% of them were on low dose aspirin therapy. 6 Hematemesis and melena were the most common presenting complains in numerous studies, 1,10,12,17 which are consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…10% had history of NSAIDS use and 5% of them were on low dose aspirin therapy. 6 Hematemesis and melena were the most common presenting complains in numerous studies, 1,10,12,17 which are consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly male predominance was found in various studies in Nepal and abroad with 80.7% , 72%, 67%, 64% respectively. 8,10,11,12 Hower ever few studies also showed female predominance in patients with UGI Bleeding. A study done from Nepal had 79% of females with UGI bleeding.…”
Section: Discussionmentioning
confidence: 98%
“…Our results confirmed this, with 59% of patients presenting with as melena and 21% of patients with melena and haematemesis simultaneously. Ar ecent study showed that the most frequent nonvariceal findings on proximal endoscopy were duodenal ulcers, representing about two-thirds of cases, followed by antral gastropathy, gastric ulcers and duodenal/gastric mass, with GERD and Mallory Weiss syndrome much less frequent (9). Our results are in accordance with this study, confirming that duodenal ulcers the leading cause of gastrointestinal bleeding, followed by gastric ulcers, hemorrhagic erosions, neoplasm and GERD.…”
Section: Discussionsupporting
confidence: 90%
“…Although peptic ulcer bleed and portal hypertension-related bleed accounts for majority of the case, non-variceal nonulcer bleeding accounts for 34-64% of all presenting cases of non-variceal UGIB in various series. [26][27][28] These include a large variety of uncommon reasons which contribute to UGB and might become reasons for misdiagnosis and sometimes lead to fatal consequences. Among this special group of patients, various pathologies found in our study were Dieulafoys lesion (0.61%), Mallory-Weiss lesions (0.38%), GI stromal tumor (0.20%), gastric polyps (0.80%), ampullary tumor (0.19%) and hemobilia (0.11%).…”
Section: Discussionmentioning
confidence: 99%